2008
DOI: 10.1016/j.placenta.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The C5b-9 Membrane Attack Complex of Complement Activation Localizes to Villous Trophoblast Injury in vivo and Modulates Human Trophoblast Function in vitro

Abstract: The complement system plays an important role in normal human pregnancy. Uncontrolled activation of this system has been associated with many disease states. We tested the hypothesis that the C5b-9 membrane attack complex (MAC) localizes to sites of villous injury and modulates trophoblast function. Placental sections from pregnancies with no complications, intrauterine growth restriction, or preeclampsia were immunostained and the surface density for MAC and fibrin was determined by morphometric analysis. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
(36 reference statements)
5
50
0
1
Order By: Relevance
“…Since the first step in the generation of sC5b-9 is the cleavage of C5 to C5a and C5b, this observation is in agreement with others who have suggested that C5a-dependent mechanisms might be of interest in placental pathology in preeclampsia (35,36). In the stratified analysis the activation of the complement system could only be demonstrated for nulliparous women.…”
Section: Discussionsupporting
confidence: 91%
“…Since the first step in the generation of sC5b-9 is the cleavage of C5 to C5a and C5b, this observation is in agreement with others who have suggested that C5a-dependent mechanisms might be of interest in placental pathology in preeclampsia (35,36). In the stratified analysis the activation of the complement system could only be demonstrated for nulliparous women.…”
Section: Discussionsupporting
confidence: 91%
“…Complement activation likely begins early in pregnancy with local effects at the placental interface, 60,61 but may ultimately become a systemic process 62 because of shedding of apoptotic or aponecrotic fetoplacental debris into the maternal circulation 63,64 with resulting systemic inflammation and endothelial activation. 14,15,17,18 Complement proteins may be filtered through an injured glomerulus and basement membrane 65 or may propagate terminal complement activation locally at the proximal tubule, 66 contributing directly to tubular inflammation (C3a, C5a) and cell death (C5b-9).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] C5a propagates a potent proinflammatory response, 13,24-26 whereas C5b-9 incorporates into cell membranes, including villous trophoblast, 27 and contributes to platelet activation, procoagulant effects, and lytic cell death. [28][29][30][31] In addition, C5a stimulates monocytes to release soluble fmslike tyrosine kinase 1, 32 which sequesters vascular endothelial growth factor and PlGF, contributing to hypertension and glomerular endotheliosis.…”
Section: Discussionmentioning
confidence: 99%